RETRACTED: Ventricular Tachyarrhythmia Risk in Paediatric/Young vs. Adult Brugada Syndrome Patients: A Territory-Wide Study - Lee, Sharen; Wong, Wing Tak; Wong, Ian Chi Kei; Mak, Chloe; Mok, Ngai Shing; Liu, Tong; Tse, Gary (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Brugada syndrome (BrS) is a cardiac ion channelopathy with a higher prevalence in Asia compared to the Western populations. The present study compared the differences in clinical and electrocardiographic (ECG) presentation between paediatric/young (≤25 years old) and adult (>25 years) BrS patients. Method: This was a territory-wide retrospective cohort study of consecutive BrS patients presenting to public hospitals in Hong Kong. The primary outcome was spontaneous ventricular tachycardia/ventricular fibrillation (VT/VF). Results: The cohort consists of 550 consecutive patients (median age of initial presentation = 51 ± 23 years; female = 7.3%; follow-up period = 83 ± 80 months), divided into adult (n = 505, mean age of initial presentation = 52 ± 19 years; female = 6.7%; mean follow-up period = 83 ± 80 months) and paediatric/young subgroups (n = 45, mean age of initial presentation = 21 ± 5 years, female = 13.3%, mean follow-up period = 73 ± 83 months). The mean annual VT/VF incidence rate were 17 and 25 cases per 1,000 patient-year, respectively. Multivariate analysis showed that initial presentation of type 1 pattern (HR = 1.80, 95% CI = [1.02, 3.15], p = 0.041), initial asymptomatic presentation (HR = 0.26, 95% CI = [0.07, 0.94], p = 0.040) and increased P-wave axis (HR = 0.98, 95% CI = [0.96, 1.00], p = 0.036) were significant predictors of VT/VF for the adult subgroup. Only initial presentation of VT/VF was predictive (HR = 29.30, 95% CI = [1.75, 492.00], p = 0.019) in the paediatric/young subgroup. Conclusion: Clinical and ECG presentation of BrS vary between the paediatric/young and adult population in BrS. Risk stratification and management strategies for younger patients should take into consideration and adopt an individualised approach.